Acute effects of foam rolling on the mechanical properties of myofascial tissues and muscle strength: a systematic review and meta-analysis - Glänzel, Marcelo Henrique (2021)
A definição do idioma inglês do trabalho foi informada por e-mail pelo autor e pela secretaria do PPG em Educação Física.